Tocilizumab in the treatment of severe and refractory parenchymal neuro-Behçet’s syndrome: case series and literature review - Liu, Jinjing; Yan, Dong; Wang, Zhimian; Yang, Yunjiao; Zhang, Shangzhu; Wu, Di; Peng, Lingyi; Liu, Zhichun; Zheng, Wenjie (Therapeutic advances in musculoskeletal disease, 2020)
Objectives: This study aimed to investigate the efficacy and safety of tocilizumab (TCZ) in severe and refractory parenchymal neuro-Behçet’s syndrome (p-NBS). Methods: We retrospectively analyzed five patients with p-NBS treated with TCZ in our center between 2013 and 2020, and six cases from literature research with the index terms “neuro-Behçet’s syndrome” and “tocilizumab” on PubMed NCBI. Results: A total of 11 patients with p-NBS were enrolled (5 males, 6 females), with a mean age of 34.5 ± 8.0 years at the onset. All the patients had parenchymal neurological lesions, six patients (54.5%) suffered from multiple lesions, and nine patients (81.8%) were disabled. Before TCZ administration, all the patients had failed conventional therapy, eight patients (72.7%) received two or more immunosuppressants, and five patients showed insufficient response or intolerance to other biologics. TCZ was administrated at 8 mg/kg every 4 weeks, with background glucocorticoids (GCs) and immunosuppressants. After a median follow-up of 13 (interquartile range, 3.5–23.5) months, all the patients achieved both clinical and radiological improvements, and the Behçet’s Disease Current Activity Form score improved significantly (3 versus 0, median, p = 0.004), the Rankin score also decreased (4 versus 2, median, p = 0.005). Levels of interleukin-6 in the cerebrospinal fluid decreased significantly in five patients (533.4 ± 389.7 pg/ml versus 34.5 ± 27.1 pg/ml, p = 0.048), after a median of two (interquartile range, 1–4) times of TCZ infusions. Furthermore, the GC dosage (per os) reduced from 69.2 ± 16.9 mg/d to 16.4 ± 16.2 mg/d (p = 0.000), and immunosuppressants were tapered in number and dosage in seven (63.6%) and four (36.3%) patients, respectively. No serious adverse events or deaths were observed during follow-up. Conclusions: TCZ is well tolerated and effective in severe and refractory p-NBS, with a favorable GC- and immunosuppressant-sparing effect. Cerebrospinal fluid interleukin-6 might be used to monitor the effects of TCZ in p-NBS.